2021
DOI: 10.11604/pamj.2021.38.388.20314
|View full text |Cite
|
Sign up to set email alerts
|

Myome, découverte fortuite ou métrorragie: qui dit mieux?

Abstract: Introduction le myome est une pathologie fréquente dans notre contexte, découverte de façon fortuite ou par des métrorragies; notre objectif était de mesurer l´association entre la taille des myomes et leur circonstance de découverte, et entre le siège des myomes et la survenue de métrorragies. Méthodes nous avons mené une étude transversale de 6 ans de janvier 2012 à décembre 2018 incluant les femmes de 18 ans et plus reçues au Centre Hospitalier Universitaire (CHU) Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…Menorrhagia accounted for 12.0% of the reasons for consultation among women with uterine fibroids. This frequency is similar to that reported by Tiemtoré-Kambou et al [11] in Burkina Faso (12.1%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Menorrhagia accounted for 12.0% of the reasons for consultation among women with uterine fibroids. This frequency is similar to that reported by Tiemtoré-Kambou et al [11] in Burkina Faso (12.1%).…”
Section: Discussionsupporting
confidence: 92%
“…These results are different depending of the study population and methodology: Balungwe et al [12] in the Democratic Republic of Congo had found 48.6% submucosal fibroid, 0.55% interstitial fibroid, 1% subserosal fibroid. Tiemtoré-Kambou et al [11] in Burkina Faso had found 6.4% submucosal fibroid, 48.9% interstitial fibroid, 11.8% subserosal fibroid.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, the lack of financial means, the fear of surgery are other factors that could explain the delay in surgical management. Our results are similar to those found by Tiemtoré et al at the CHU of Bogodogo in Burkina [11] and Koffi et al [12] in Côte d'Ivoire which found respectively an average age of 37 years and 37.5 years.…”
Section: Uterine Effractionsupporting
confidence: 92%